2009
DOI: 10.1007/s10468-009-9128-7
|View full text |Cite
|
Sign up to set email alerts
|

Hopf Algebras of Dimension 16

Abstract: We complete the classification of Hopf algebras of dimension 16 over an algebraically closed field of characteristic zero. We show that a non-semisimple Hopf algebra of dimension 16, has either the Chevalley property or its dual is pointed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…This proposition has proved extremely useful in other attempts at classification, for example in [12,22,26]. A natural question is whether an analogue holds for Hopf algebras generated by simple subcoalgebras of dimension p, p an odd prime; see [5].…”
Section: Proposition 41 Let a Be A Finite Dimensional Non-semisimplementioning
confidence: 99%
See 1 more Smart Citation
“…This proposition has proved extremely useful in other attempts at classification, for example in [12,22,26]. A natural question is whether an analogue holds for Hopf algebras generated by simple subcoalgebras of dimension p, p an odd prime; see [5].…”
Section: Proposition 41 Let a Be A Finite Dimensional Non-semisimplementioning
confidence: 99%
“…Two nonisomorphic nonpointed self-dual Hopf algebras of dimension 16 with coradical A 8 were described by Cȃlinescu, Dȃscȃlescu, Masuoka and Menini in [18] where the classification of Hopf algebras of dimension 16 with the Chevalley property is completed. Very recently García and Vay [26,Theorems 1.2,1.3] showed that the list of isomorphism classes above exhausts all possibilities for dimension 16, in other words, every Hopf algebra of dimension 16 has the Chevalley property or its dual is pointed.…”
Section: Hopf Algebras Of Dimension 16mentioning
confidence: 99%
“…A morphism ψ : A# f H → A# f H stabilizes A if and only if ψ(a#1 H ) = a# 1 H , for all a ∈ A. Taking into account the formula for ψ given by (14), we obtain that ψ stabilizes A if and only if u(a (1) )# p(a (2) ) = a# 1 H , i.e. u(a) = a and p(a) = ε A (a)1 H , for any a ∈ A.…”
Section: Corollary 23 Let ψ : A# F H → A# F H Be a Hopf Algebras Mamentioning
confidence: 99%
“…On the other hand, there is no efficient cohomology theory for arbitrary Hopf algebras, similar to the one from group theory, to make a direct description of H 1 * (H, A) possible. One of the few examples known is [14,Lemma 2.8] where it is proved that any extension of H 4 by H 4 is equivalent to the trivial extension…”
Section: Introductionmentioning
confidence: 99%
“…By [HN,Lemma A.2], there exists an H -module isomorphism ϕ : P → S 2 P such that ϕ p n = id. It follows from [Ng4,Lemma 1.3] that Tr(ϕ) = 0.…”
Section: Lemma 14 (Seementioning
confidence: 99%